2006
DOI: 10.1182/blood-2005-04-1505
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the plasminogen activator inhibitor-2 in cells expressing the ZNF198/FGFR1 fusion kinase that is involved in atypical myeloproliferative disease

Abstract: The ZNF198/FGFR1 fusion kinase associated with an atypical myeloproliferative disease is constitutively activated and regulates several STAT transcription factors. We used oligonucleotide microarrays to compare the gene-expression profiles between HEK-293 cells that stably express either the ZNF198/FGFR1 chimeric protein or the wild-type ZNF198 gene. Expression of the plasminogen activator inhibitor-2 (PAI-2/SERPINB2) was highly increased in cells expressing the fusion gene. Western blot analysis demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…The infection efficiency, as estimated by flow cytometry for GFP-positive cells, was approximately 16%, and the expression of the fusion protein in these transduced BM cells was confirmed either by Western blotting using the FGFR1 antibody described by Kasyapa et al 29 or PCR (data not shown). After 5-day culture, these infected BM cells were transplanted into recipient female mice ( Figure 1B).…”
Section: Znf198-fgfr1 Induced Both Myeloproliferative Disorder and T-mentioning
confidence: 93%
“…The infection efficiency, as estimated by flow cytometry for GFP-positive cells, was approximately 16%, and the expression of the fusion protein in these transduced BM cells was confirmed either by Western blotting using the FGFR1 antibody described by Kasyapa et al 29 or PCR (data not shown). After 5-day culture, these infected BM cells were transplanted into recipient female mice ( Figure 1B).…”
Section: Znf198-fgfr1 Induced Both Myeloproliferative Disorder and T-mentioning
confidence: 93%
“…An additional pathway involving the plasminogen activator inhibitor 2 gene has also been implicated in cells with the ZNF198-FGFR1 fusion gene. By gene expression profiling, Kasyapa et al [68] demonstrated overexpression of plasminogen activator inhibitor 2, a proteinase inhibitor that prevents targeted proteolytic degradation, which function is not observed in activated native FGFR1 signaling. As such, plasminogen activator inhibitor 2 plays a role in protein stabilization but also confers resistance to tumor necrosis factor α-induced apoptosis; this latter feature is proposed to contribute to the aggressive nature of the cells carrying the ZNF198-FGFR1 fusion.…”
Section: Potential Role Of Fgfr1 In Oncogenesismentioning
confidence: 98%
“…Xiao et al [9,24] demonstrated that the Nterminus proline-rich motifs and not the zinc finger motifs of ZNF198 are required for oligomerization of the fusion protein. Whereas native FGFR1 is tethered to the cell membrane, the ZNF198-FGFR1 fusion protein and other FGFR1 translocation products are found in the cytoplasm due to a loss of a putative nuclear localization signal located in the C-terminus end of ZNF198 [61,67,68]. The adaptor protein FRS2α binds to a sequence recognition motif of native FGFR1 near the juxtamembrane domain, between amino acids 407 and 433 [69].…”
Section: Molecular Featuresmentioning
confidence: 99%
“…Sequestration of these phosphorylated effectors by the 14-3-3 family of conserved, phosphoserine/threonine-binding proteins has been suggested to be an important mechanism by which ZNF198-FGFR1 abrogates apoptosis [11]. ZNF198-FGFR1 induces overexpression of the plasminogen activator inhibitor 2 (PAI-2/SERPINB2) in Ba/F3 and HEK-293 cells, and this has also been suggested to play a role in anti-apoptotic signalling [12]. …”
Section: Fgfr1 Fusion Genesmentioning
confidence: 99%